SISTEM PENGONTROLAN SUHU DAN KELEMBABAN PADA ALAT PENGONTROL PENETASAN TELUR AYAM MENGGUNAKAN METODE KONTROL ON-OFF - Nandito Ardaffa Putra; n/a Rahmadwati; Goegoes Dwi Nusantoro (Jurnal Mahasiswa TEUB, 2022)
This study describe about design an egg incubator with temperature and humidity control. This study used the on-off control method to design an egg incubator with temperature and humidity control. The output of this control is to determine whether the lights and humidifier will turn off or on. This research has resistance to design, characterization, and testing. The setpoint used was temperature 37℃ on day 1 to and 18 and 36℃ after day 18. Then, the humidity was 60%RH on days 1 to 18 and 75%RH after day 18. Based on the test, it was found that the temperature control system was made using an on-off controller on the 1st to 18th day having ?? = 1910s, ?? = 1710s, ??? = 0,353% , after the 18th day it had ?? = 160s, ?? = 160s, ??? = 0,351%. The humidity control system was made using an on-off controller on days 1 to 18 having ?? = 1670s, ?? = 1870s, ??? = 0,562%. a